The song of Pentecost - Corbett, W. J.; Ursell, Martin (England : Puffin Books, 1984)
Recounts the many harrowing adventures of a group of mice and their leader Pentecost who set out to help Snake regain his inheritance and find a new home for themselves in the Lickey Hills.
Keywords: Mice -- Juvenile fiction; Animals -- Juvenile fiction